Students’ science process skills and interpersonal intelligence in biology learning using guided inquiry - N. Nopiya; Anna Fitri Hindriana; S. Sulistyono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Teacher-centered learning has no ability in empowering students’ science process skills and interpersonal intelligence. This study aimed at analyzing the effect of guided inquiry on students’ Science Process Skills (SPS) and Interpersonal Intelligence (II). This quasi-experiment used nonequivalent control group design. This study involved control and experimental classes of eleventh graders in biology class in which the material learnt was respiratory system. The SPS data was collected using test instrument, whereas the II data was gained using observation sheet. The analysis results informed that the students who joint the guided inquiry class possessed the better competencies, both in their SPS (p = 0.04) and II (p = 0.001). Therefore, the guided inquiry significantly contributes toward the improvement of students’ SPS and II. The findings of this research can be the considerable information to creat the learning which acommodates students’ SPS and II.